Wear of different materials for total hip replacement under adverse stop-dwell-start in vitro wear simulation conditions. (December 2018) - Hadley, Megan; Hardaker, Catherine; Isaac, Graham; Fisher, John
Hip simulation is a common technique for pre-clinical evaluation of wear performance of total hip arthroplasty. Standard techniques replicate kinematics of walking patterns of a typical patient. Attention has focussed in developing simulations of other typical patient daily activities to improve accuracy of wear predictions. A method for simulating stop-dwell-start motion during patient walking and the effect on 36-mm metal-on-metal total hip arthroplasty was previously presented by the authors. This study sought to extend the previous work to look at the effect of these conditions on ceramic-on-ceramic, metal-on-polyethylene and ceramic-on-polyethylene bearings. Two stop-dwell-start protocols were used: one reproducing average patient movement patterns and one examining more severe conditions. For all materials tested, no significant increase in wear was observed under average stop-dwell-start conditions, suggesting the bearing types tested are robust to this type of activity. A significant increase in wear was observed for metal-on-metal, metal-on-polyethylene and ceramic-on-polyethylene bearings under severe stop-dwell-start conditions, this was attributed to depletion of lubricant in the bearing during the dwell period. A greater relative increase in wear was observed for metal-on-metal bearings compared with metal-on-polyethylene and ceramic-on-polyethylene bearings. This may be explained by the contributions of the different lubrication mechanisms in each bearing type. Wear of ceramic-on-ceramic was very low in all tests, suggesting normal measurement variation was masking any effect of the adverse conditions. It was not possible to determine any effect of the different activities. These results emphasise the importance of exploring adverse patient activity simulations. The increase in wear rate associated with an adverse activity such as seen in stop-dwell-start motion, has to be considered in the context of the frequency of the adverse activity cycle relative to other activities such as standard continuous walking, to determine the impact on the total wear in a given time period.